Respuesta :

Answer:

[tex]x^2+4x-12=0[/tex]

Step-by-step explanation:

If a equation has two zeros x=a and x=b then equation can be written as

[tex](x-a)(x-b)=0[/tex]

similarly if a equation has two zeros at x = −6 and x = 2

then equation can be written as

[tex](x+6)(x-2)=0[/tex]

[tex]x^2+6x-2x-12=0[/tex]

[tex]x^2+4x-12=0[/tex]

Therefore [tex]x^2+4x-10[/tex] is required equation

Answer:

x²+4x - 12 = 0 is the answer.

Step-by-step explanation:

We have to drive the equation that is true for x = -6 and x = 2.

If the equation has  two zeros then equation is of the form as below:

(x-c)(x-d) = 0

We simplify the equation when the equation has zeros at x = -6  and x= 2.

(x-(-6))(x-2)=0

(x+6)(x-2) = 0

x²-2x+6x-12 = 0

x²+4x - 12 = 0

x²+4x - 12 = 0 is the answer of given expression.